Transport into the 80s papers presented at the conference sponsored by the Institution of Civil Engineers and the UK Government Department of Transport in conjunction with the Hong Kong Institution of Engineers and the British Overseas Trade Board : Hong Kong, 15-19 February 1982. (Thomas Telford, 1982)
This title is part of the ICE Publishing complete digital collection - helping ensure access to essential engineering content from past to present. Proceedings of a conference held in Hong Kong on 15-19 February 1982.